2015
DOI: 10.1073/pnas.1508573112
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic dosage lethality in the human metabolic network is highly predictive of tumor growth and cancer patient survival

Abstract: Synthetic dosage lethality (SDL) denotes a genetic interaction between two genes whereby the underexpression of gene A combined with the overexpression of gene B is lethal. SDLs offer a promising way to kill cancer cells by inhibiting the activity of SDL partners of activated oncogenes in tumors, which are often difficult to target directly. As experimental genome-wide SDL screens are still scarce, here we introduce a network-level computational modeling framework that quantitatively predicts human SDLs in met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 48 publications
0
39
0
Order By: Relevance
“…Although SDL has been used to identify protein targets of enzymes (82,100,101) and to identify specific subsets of genes within chromosome segregation mutants (29), it is underused to uncover genetic contexts that could selectively target cancer cells with elevated levels of a specific gene (26,27,102). SDL screens therefore represent a powerful approach for fast and easy identification of candidate chemotherapeutic drug targets within the context of dCIN gene overexpression that could enable targeted elimination of these cells.…”
Section: Sdl Screens As a Platform To Identify Therapeutic Targets Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Although SDL has been used to identify protein targets of enzymes (82,100,101) and to identify specific subsets of genes within chromosome segregation mutants (29), it is underused to uncover genetic contexts that could selectively target cancer cells with elevated levels of a specific gene (26,27,102). SDL screens therefore represent a powerful approach for fast and easy identification of candidate chemotherapeutic drug targets within the context of dCIN gene overexpression that could enable targeted elimination of these cells.…”
Section: Sdl Screens As a Platform To Identify Therapeutic Targets Inmentioning
confidence: 99%
“…Most SL approaches focus on exploiting specific somatic mutations or deletions in cancer driver genes; however, there are just as many amplified regions as deleted regions in cancer genomes (17). Thus, we propose using synthetic dosage lethality (SDL), which is SL with an amplified and/or overexpressed gene, as an approach to selectively target tumors that overexpress dCIN genes (26,27). SDL occurs when the overexpression of a gene is not lethal in a wild-type background but in conjunction with a second site nonlethal mutation causes lethality (28)(29)(30).…”
mentioning
confidence: 99%
“…For instance, when glucose is completely oxidized to carbon dioxide to generate maximal amounts of ATP, it can no longer be utilized as biomass precursors for amino acid and nucleotide biosynthesis. Therefore, we reasoned that the distribution of metabolic flux can only be comprehensively determined by multiple biological objectives ( Fig 1A), including (1) maximization of biomass production, which is frequently considered as the only objective in previous FBA studies of cancer cells Gatto et al, 2015;Megchelenbrink et al, 2015;Yizhak et al, 2014a), (2) maximization of ATP hydrolysis, which is considered as the objective in some FBA studies of non-malignant cells Yizhak et al, 2014b), (3) minimization of total abundance of metabolic enzymes, which is an analogue of the solvent capacity constraint Vazquez et al, 2010), and (4) minimization of total carbon uptake (Savinell and Palsson, 1992). These four objectives reflect different aspects of metabolic demand, covering both maximization of biomass yield and minimization of energy cost.…”
Section: Four-objective Optimization Model For Cancer Metabolismmentioning
confidence: 99%
“…While traditional methods are suited to dissect limited numbers of metabolic pathways, systems biology is a powerful tool to study metabolism from a global perspective . Within the field of cancer metabolism, analyses of genome-scale metabolic models (GSMMs) Thiele et al, 2013) enabled researchers to elucidate the plausible mechanism of Warburg effect , quantify efficacies and side effects of cancer therapeutics (Agren et al, 2014;Folger et al, 2011;Shaked et al, 2016;Yizhak et al, 2014a;Yizhak et al, 2014b), and unravel context-dependent functionality of metabolic enzymes during tumor progression Megchelenbrink et al, 2015;Rabinovich et al, 2015;Tardito et al, 2015). Among various strategies, flux balance analysis (FBA) exhibits itself as a highly effective approach to analyze GSMMs (Orth et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous investigations have shown that the overall numbers of functionally active SLs and SDLs 65 in a given tumor sample are highly predictive of patient survival (Megchelenbrink et al, 2015). These 66 three interaction types however represent just the 'tip of the GI iceberg', as there are many additional 67 types of GI that can be defined at a conceptual level, and whose systematic exploration may have 68 important functional ramifications for cancer therapy.…”
mentioning
confidence: 99%